How do Typological Studies Explain the Semantic Changes of English Complex Prepositions? - Yamaguchi Kazuyuki (Topics in Linguistics, 2014)
The purpose of this study is to investigate the semantic changes of English complex prepositions and to argue that they are explained on the basis of two possible mechanisms of semantic change.